La « connexion hamburger » appliquée à l’Amazonie brésilienne. Décryptage de l’ « effet papillon » entre consumérisme carné et déboisement - Guillaume Marchand (Confins)
According to the “hamburger connection” concept, one of the lasts rainforest regions of the earth would be directly menaced by our excessive consumption of beef meat. The idea is not very new, it was formulated in the 1980 by the environmentalist N. Myers to explain the intensification of deforestation in Central America. Twenty-four years after, a group of researcher of the CIFOR excavated it for Brazilian Amazon’s case. The media and ecologist ONG’s divulgated quickly the information, with, sometimes, callings to boycott of Brazilian meats and also European or North-American restaurants which serve its. If the identification of causes/consequences links between our daily lifestyles and global environmental impacts is praiseworthy, the objective is to make progress consciences, there are sometimes some simplifications on the nature and the magnitude of these phenomena. With the study of the spatial structures evolutions of Brazilian livestock commodity chains, and more specifically Amazonian chains since the opening of the agrarian frontier (1970’s), this article aim to evaluate how the different ecosystems of the region have suffered of our carnivorous instincts. We will see that the international hamburger connection is a phenomenon with numerous ramifications, not consuming every times tropical dense forests but more often savannas and transition forest areas.